The Secrecy and Publicity of Diplomacy: Questions to the Theory of Public Diplomacy - Witri Elvianti (Andalas Journal of International Studies (AJIS))
Just a few weeks after the terrorist attacks of September 11th, and soon after US troops started to attack Afghanistan, George Bush expressed his disappointment toward the way the Muslim world perceives the American way of life and culture. Assuming that the 9/11 terrorist attack was a symbol of struggle against America’s hegemony Bush blamed the failure of US public diplomacy to promote to the Muslim world the image of a friendly and democratic nation state. It sent a message that both promoting positive image and controlling the message are a highly complex task. The complexity of public diplomacy consequently raises such a theoretical dispute. From a traditional perspective, scholars have questioned the suitability of public diplomacy to promote a states’ soft power, and have cited US public diplomacy as an example of failure. The revisionists, on the other hand, seek to maintain and even improve the practice of public diplomacy by arguing that it is more that it is more pertinent to comprehend the strategy rather than to perpetuate the blame.  The dispute on public diplomacy is threefold: first, whether public diplomacy is defined as any diplomatic activities of or by the public; second, whether diplomacy should really be addressed to the public; and third, if the public is always diplomatic. This essay will argue that while the traditionalist criticisms could be valid, particularly in the context of the US experience, these arguments do not reduce the value of public diplomacy. Such diplomacy requires a two-way relationship and integrated approach.